Influence Temperature and Holding Time of Empty Fruit Bunch Slow Pyrolysis to Phenolic in Biocrude Oil - Anton Irawan; Teguh Kurniawan; Hafid Alwan; Darisman Darisman; Dina Pujianti; Yazid Bindar; Asep Bayu Dani Nandiyanto; Muhammad Saifullah Abu Bakar (Universitas Muhammadiyah Magelang, 2021)
Indonesia has an abundance of biomass from agricultural, plantation, and domestic waste products. Biomass can be converted into fuels and chemicals that are environmentally friendly. Empty fruit bunches (EFB) are biomass from abundant palm oil processing. Pyrolysis was a thermal process with free oxygen at temperatures between 400-600Â°C. Generally, pyrolysis was carried out under fast pyrolysis to produce a product that leads to bio-crude oil. One of the main components of bio-crude oil was phenol, which had been produced from further processing of crude oil. With the limitations of crude oil, the production of phenol from biomass pyrolysis was an option for the future, especially for fuels and fuel additives. Thus, it is necessary to investigate the effect of heating rate, temperature pyrolysis, and holding time on pyrolysis products including phenols in bio-crude oil. Slow pyrolysis of EFB was performed at various parameters, including temperatures (400, 450, and 500Â°C) and holding time (5, 10, and 15 min). Slow pyrolysis of oil palm EFB with variations in temperature and holding time has been carried out by producing liquid between (40 - 42 %weight), gas (19 ”“ 21 % weight), and solid products (38 ”“ 39 % weight). Biocrude oil liquid product showed the highest yield compared to biochar and bio pyrolysis gas. Temperature plays an important role in controlling the production of bio-crude oil as a liquid product, including a component in bio-crude oil. Phenol recovery was more affected by temperature instead of holding time.